Effectiveness of Chair Aerobics and Swiss Ball in Primary Dysmenorrhoea: Life Sciences-Physiotherapy for Better Pain Management - Mintu Merin Koshy; Dr. Smita Chandrakant Patil; Dr. Chandrakant Babaso Patil; Dr. Khushboo Trishant Chotai (International Journal of Life Science and Pharma Research, 2022)
Dysmenorrhoea is the pain that occurs during menstruation. It is one of the common gynaecological disorders that affects women’s quality of life and day to day activities. Primary dysmenorrhoea (PD) is characterised by cramping lower abdomen pain that may radiate to the lower back and upper thigh. Associated complaints include stress, depression, headache and diarrhoea. The overall prevalence of primary dysmenorrhoea is about 60% - 90%. There are many conservative treatments for primary dysmenorrhoea conditions but more effective one is not yet known. Hence it is necessary to find the effectiveness of chair aerobics and swiss ball in primary dysmenorrhoea. The study was conducted with 50 subjects in and around Krishna Institute of Medical Sciences campus who have primary dysmenorrhoea symptoms. The subjects are divide into two groups, Group A and B. Group A were given chair aerobics exercises and Group B were given swiss ball exercises. The result of this study was analysed by the basis of pre-test and post-test assessment of VAS and VMSS. Arithmetic mean & standard deviation was calculated for each outcome measure. MS Excel was used for drawing various graphs with given frequencies. According to the pre-test and post-test analysis the result showed that swiss ball exercises are statistically significant in reducing VAS and VMSS score than chair aerobics exercises in primary dysmenorrhoea. On the basis of the results it is concluded that the swiss ball exercises are more effective than chair aerobics in decreasing pain and improving quality of life in primary dysmenorrhoea.